Scaling the assessment of emotion regulation effectiveness with a low-cost psychophysiological system - Moreira, Pedro Miguel Silva (2019)
In this work, we assessed the reliability of a low-cost psychophysiological system - the James One device - to monitor the electrodermal activity during an emotion induction paradigm. We observed that during emotional expression in response to negative stimuli, participants displayed increased amplitudes of the skin conductance responses, in comparison to the natural observation of neutral pictures and to emotion regulation. These results are in accordance with previous findings obtained with medical-grade devices. Altogether, these results highlight the potential of this system to be implemented in large-scale settings, particularly in psychopathological conditions marked by severely impaired emotion regulation ability, such as depression and anxiety.